2005
DOI: 10.1029/2004jb003343
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in elastic properties and the evolution of large continental strike‐slip faults

Abstract: [1] We use geodetic studies to quantify several cases of significant asymmetry in interseismic and coseismic effects along large continental strike-slip faults using simple two-dimensional edge dislocation models. We first show that asymmetric elastic loading characterizes the present Main Marmara Fault, a portion of the North Anatolian Fault along the northern margin of the Sea of Marmara. The ratio of asymmetry there is about 10. This ratio is even larger, about 30, along the northern Sumatra fault near lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…However, the inferred magnitude of the rigidity contrasts exceeds high-end estimates from seismic tomography of a factor of 2-2.5 24,25 . The total inferred contrast across the San Andreas and San Jacinto faults is about a factor of 5 to 10, significantly larger than any seismically determined lateral variations in elastic moduli, but comparable to inferences based on geodetic data from other localities 15 . An alternative possibility is that the Quaternary fault traces are not indicative of the fault positions below the brittle layer.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…However, the inferred magnitude of the rigidity contrasts exceeds high-end estimates from seismic tomography of a factor of 2-2.5 24,25 . The total inferred contrast across the San Andreas and San Jacinto faults is about a factor of 5 to 10, significantly larger than any seismically determined lateral variations in elastic moduli, but comparable to inferences based on geodetic data from other localities 15 . An alternative possibility is that the Quaternary fault traces are not indicative of the fault positions below the brittle layer.…”
mentioning
confidence: 61%
“…Asymmetric patterns of interseismic velocities have been reported elsewhere on the SAF and other major strike-slip faults 15,20,21 , and often attributed to lateral variations in crustal rigidity 14,15 . Significant (a factor of two) variations in the effective shear modulus were also reported for kilometer-wide damage zones around several faults in southern California 11,22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in the Ventura Basin of southern California [ Donnellan et al , 1993; Hager et al , 1999] has shown that an elastically weak sedimentary cover can obscure locking depth and slip rates estimates based on geodetic data. Thus lateral and vertical variations in elastic and viscous properties in the Salton Trough may be important in influencing the form of surface deformation [ Le Pichon et al , 2005] and therefore our interpretation of geodetic data.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest approach relies on two-dimensional cross-sectional models of geodetic velocity profiles, which allow examination of slip partitioning or material heterogeneity for specific sections of the plate boundary [Malservisi et al, 2001;Johnson and Segall, 2004;Le Pichon et al, 2005;Argus et al, 2005;Hilley et al, 2005;Fay and Humphreys, 2005;Schmalzle et al, 2006;Fialko, 2006;Johnson et al, 2007]. For the SJF-SAF system, the elastic deep slip-driven fault model of Fialko [2006] finds slip rates of 25 ± 3 and 19 -21 mm/a for the SAF and SJF, respectively, whereas the elastic and viscoelastic models of Fay and Humphreys [2005] find rates of about 22-23 and 14-15 mm/a for the SAF and SJF, respectively (Table 1).…”
Section: Introductionmentioning
confidence: 99%